1996
DOI: 10.1103/physreve.53.5169
|View full text |Cite
|
Sign up to set email alerts
|

Small-angle neutron scattering from multilamellar lipid bilayers: Theory, model, and experiment

Abstract: Small-angle neutron scattering data obtained from fully hydrated, multilamellar phospholipid bilayers with deuterated acyl chains of different length are presented and analyzed within a paracrystalline theory and a geometric model that permit the bilayer structure to be determined under conditions where the lamellar layers are coupled and fluctuating. This theory provides structural information in the region of the solid-fluid bilayer phase transition without invoking the usual decoupling of the scattering int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
65
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 45 publications
7
65
0
Order By: Relevance
“…For the longer tail lengths, this maximum disappears. 48,50 We observe a large increase of the bilayer thickness for all lipid tail lengths, caused by a simultaneously increase of the hydrocarbon thickness and the thickness of the headgroup region. We do not observe a maximum in the curve for the shorter lipids.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For the longer tail lengths, this maximum disappears. 48,50 We observe a large increase of the bilayer thickness for all lipid tail lengths, caused by a simultaneously increase of the hydrocarbon thickness and the thickness of the headgroup region. We do not observe a maximum in the curve for the shorter lipids.…”
Section: Discussionmentioning
confidence: 92%
“…2,24 Experimental work and theories suggest that the swelling could be caused by increased interactions between bilayers due to changes in the Helfrich undulation forces. [45][46][47][48][49][50] Approaching the transition temperature T m , the bilayer has a reduced bending rigidity and as a result the fluctuations of the bilayer increase. Due to these increased bilayer fluctuations the steric repulsion between bilayers increases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, quantitative use of the scattering intensity for structure determination requires correction for the fluctuations endemic in such systems [1]. A harmonic theory [2,3] that predicts power law tails in the scattering line shapes fits membrane data very well [4,5], but the anharmonicities that are inherent in realistic potentials have remained a concern for quantitative interpretation [6,7], even though a renormalization group analysis suggested that such effects are small [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, quantitative use of the scattering intensity for structure determination requires correction for the fluctuations endemic in such systems [1]. A harmonic theory [2,3] that predicts power law tails in the scattering line shapes fits membrane data very well [4,5], but the anharmonicities that are inherent in realistic potentials have remained a concern for quantitative interpretation [6,7], even though a renormalization group analysis suggested that such effects are small [8].Stacks of bilayers are also much studied because they provide ideal environments to study fundamental interactions between bilayers, especially since the range of interbilayer distances a can be systematically varied by applying osmotic pressure P [9]. The corresponding theory [10] is an approximate first-order perturbation theory that again relies on harmonic assumptions, such as the normality of the probability distribution function of the interbilayer spacing.…”
mentioning
confidence: 99%
“…2. swelling in terms of Helfrich's undulations forces, 22,23 increase in conformational order of the hydrocarbon chains, 24,25 increase in the water thickness, 1 or increase in head-group layer thickness. Moreover, the recent experimental data of Mason et al 8 show that anomalous swelling even occurs in systems that do not form a rippled phase.…”
mentioning
confidence: 99%